TSPAN4-positive migrasome derived from retinal pigmented epithelium cells contributes to the development of proliferative vitreoretinopathy - Liangjing Wu; Shuai Yang; Hui Li; Yao Zhang; Le Feng; Conghui Zhang; Jiayi Wei; Xunyi Gu; Guotong Xu; Zhaoyang Wang; Fang Wang (Journal of Nanobiotechnology, 2022)
Abstract Background Proliferative vitreoretinopathy (PVR) is a blind-causing disease initiated by the activation of retinal pigmented epithelium (RPE) primarily induced by TGF-β families. Migrasome is a recently discovered type of extracellular vesicle related to cell migration. Results Here, we used ex vivo, in vitro, and in vivo models, to investigate the characteristics and functions of migrasomes in RPE activation and PVR development. Results indicated that the migrasome marker tetraspanin-4 (TSPAN4) was abundantly expressed in human PVR-associated clinical samples. The ex vivo model PVR microenvironment is simulated by incubating brown Norway rat RPE eyecups with TGF-β1. Electron microscope images showed the formation of migrasome-like vesicles during the activation of RPE. Further studies indicated TGF-β1 increased the expression of TSPAN4 which results in migrasome production. Migrasomes can be internalized by RPE and increase the migration and proliferation ability of RPE. Moreover, TSPAN4-inhibited RPE cells are with reduced ability of initiating experimental PVR. Mechanically, TSPAN4 expression and migrasome production are induced through TGF-β1/Smad2/3 signaling pathway. Conclusion In conclusion, migrasomes can be produced by RPE under PVR microenvironment. Migrasomes play a pivotal role in RPE activation and PVR progression. Thus, targeting TSPAN4 or blocking migrasome formation might be a new therapeutic method against PVR.